Money Demand Analysis through Business Cycle in Indonesia - Isna Melati; Mahrus Lutfi Adi Kurniawan (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
There is still debate about the role of monetary aggregates (money demand) and their nature in the domestic economy, whether there is a direct affect and indirect affect. After the 2008 crisis, monetary aggregates became a monetary policy tool that played an important role in maintaining domestic economic stability. This study aims to examine macroeconomic variables on the demand for money in Indonesia from 2000Q1-2021Q4 using the VECM approach. The business cycle is used as a proxy for the income variable with the Hodrick-Prescott Filter method on the GDP variable. The results show that income has a high degree of variability in the demand for money and there is a sensitivity in the response of the demand for money to fluctuations in domestic interest rates. The implication of this research the application of domestic interest rates at the lowest level can encourage income which can increase the demand for money in Indonesia.